ANALISIS KONSTRUKSI MAKNA DENOTASI DAN KONOTASI IKLAN TRANSPORTASI ONLINE DI MEDIA YOUTUBE - Irwan Soulisa (SOSCIED, 2026)
The rapid development of digital technology has encouraged online transportation companies to utilize YouTube as a promotional platform to build brand image through various visual, verbal, and symbolic signs. This study aims to describe the denotative, connotative, and mythical meanings embedded in the YouTube advertisements of Gojek, Grab, and Maxim by employing Roland Barthes' semiotic approach. This research adopted a descriptive qualitative method. The research data consisted of visual, verbal, and audio elements contained in the advertisement videos of Gojek, Grab, and Maxim uploaded to YouTube. Data were collected through observation, documentation, and the identification of sign elements within the advertisements. Subsequently, the data were analyzed through the stages of sign identification, interpretation of denotative, connotative, and mythical meanings, and conclusion drawing. The findings indicate that, at the denotative level, the advertisements depict the use of online transportation services, including the booking process, passenger pick-up, and parcel delivery. At the connotative level, each advertisement constructs a distinct brand image: Maxim is portrayed as a practical and easily accessible service; Grab emphasizes safety, affordability, and support for business activities; while Gojek is presented as a mobility solution that offers comfort, hope, and emotional closeness to the community. At the mythological level, all three advertisements construct the perception that online transportation symbolizes a modern lifestyle characterized by convenience, efficiency, and the integration of digital technology into everyday life. The findings further demonstrate that online transportation advertisements function not only as promotional media but also as instruments for constructing social and cultural meanings as well as brand identity through the strategic use of signs conveyed to the public